2007
DOI: 10.1007/s00125-007-0752-7
|View full text |Cite
|
Sign up to set email alerts
|

Apolipoprotein A-I stimulates AMP-activated protein kinase and improves glucose metabolism

Abstract: Aims/hypothesis In humans, one of the hallmarks of type 2 diabetes is a reduced plasma concentration of HDL and its major protein component, apolipoprotein A

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
127
1
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 135 publications
(137 citation statements)
references
References 33 publications
8
127
1
1
Order By: Relevance
“…Student t-test was used to compare the groups with the same diet (*Po0.05 and **Po0.01). Please note that part of the data from the groups of mice fed with NC has been previously reported (Han et al, 2007). However, these data are included here for better comparison with the mice fed with HFD.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Student t-test was used to compare the groups with the same diet (*Po0.05 and **Po0.01). Please note that part of the data from the groups of mice fed with NC has been previously reported (Han et al, 2007). However, these data are included here for better comparison with the mice fed with HFD.…”
Section: Resultsmentioning
confidence: 99%
“…It has long been postulated that Apoa-I and HDL levels are inversely associated with the incidence of MS, which are associated with an increased risk of type II diabetes and cardiovascular diseases (Dandona et al, 2005;Eckel et al, 2005). Recently, Han et al (Han et al, 2007) showed that Apoa-I À/À mice have impaired glucose tolerance (IGT) and increased body fat because of the fact that Apoa-I activates AMP-activated protein kinase (AMPK) and thus affects the energy and glucose metabolism of the cell. Given the fact that variations in both host genetics and gut microbiota predispose animals to MS, it is compelling to investigate the relative contributions of diet-disrupted gut microbiota and host gene mutations to MS development.…”
Section: Introductionmentioning
confidence: 99%
“…HDLs have antidiabetic properties. They reduce hyperglycaemia via their capacity to decrease pancreatic β-cell apoptosis (Abderrahmani et al 2007;Fryirs et al 2010;Rutti et al 2009) and to stimulate glucose disposal in skeletal muscle (Han et al 2007). They decrease dyslipidaemia via lowering adipocyte lipolysis (Van Linthout et al 2010a) and induce insulin sensitivity (Berg et al 2001) via upregulating the expression of adiponectin (Van Linthout et al 2010a), which abrogates the development of hyperinsulinaemia.…”
Section: Human Apo A-i Gene Transfer Attenuates Diabetic Cardiomyopathymentioning
confidence: 99%
“…Anti-inflammatory and antioxidative functions of HDLs have been described in addition to the innate immune function of HDLs as a defense against viral, bacterial, and parasitic infections (6). In addition, HDLs are directly involved in glucose metabolism through insulin secretion in pancreatic b-cells (13) and improvement of insulin sensitivity (14,15). Although little is known about the role of apoA-I in the development of T2D, the findings of some recent studies are in agreement with the observations described in this study.…”
Section: European Journal Of Endocrinologymentioning
confidence: 99%